Consideration of quality control standards through splitting tensile strength evaluation of plate-like improved soil - SINDETE, Mathiro Jose; Usui, Hirofumi; Hino, Takenori (International Association of Lowland Technology, 2024)
The Saga lowlands in Kyushu, Japan, face significant settlement issues in embankments due to the high compressibility, sensitivity, and low permeability of Hasuike and Ariake clays. To address these challenges, a combination of columnar and plate-like ground improvement techniques is used. However, natural disasters, such as earthquakes, have revealed the inadequacies of current quality control methods, leading to structural failures. This study aims to enhance quality control for plate-like improved soil constructed using slurry methods by organizing field data based on design standard tensile strength (σtk), field standard tensile strength (σtf), and lab standard tensile strength (σtl). It also investigates the relationship between unconfined compressive strength (qu) and splitting tensile strength (σt) through laboratory experiments. Hasuike clay was treated with varying binder dosages and a water-cement (W/C) ratio of 1, to evaluate the strength ratio (α) between qu and σt after 28 days of curing. Key findings show that setting σtl at 2.0 times σtf effectively minimizes the risk of falling below σtk, thereby enhancing soil performance. Laboratory results indicate that the strength ratio α for Hasuike clay varies with cement content, showing mean values between 0.12 and 0.15, with optimal combinations yielding values from 0.21 to 0.28, which is higher than the empirical standard of 0.1. Conversely, less favorable combinations with minimum values resulted in α values between 0.05 and 0.07, which should be carefully considered when designing plate-like improved soil. These results underscore a statistical and systematic approach to quality control in ground improvement projects to ensure the durability and stability of soil structures in challenging environments like the Saga lowlands.